Minimizing the Scarcity of Ulama in The Disruption Era: Existence and Strategy of Islamic Higher Education Institutions in Preparing Ulama - Yusri, Dairina; Hanafiah, Muhammad Ali; Lubis, Masruroh (STAI Serdang Lubuk Pakam, 2024)
The scarcity of ulama is a major concern in Islamic education because the higher education system is no longer considered adequate to produce graduates with a deep understanding of religion according to the demands of the times. This research aims to analyze the ulama regeneration program in Medan, focusing on the existence, materials, learning strategies, and obstacles faced. This research was conducted at the Higher Education for the Cadre of Ulama of the Indonesian Ulama Council of North Sumatra and Al-Washliyah University. The research method used is qualitative with a phenomenological approach. Data analysis uses Miles and Huberman techniques supported by Atlas Ti software. The results revealed that in Islamic higher institutions in Medan City there are two ulama regeneration institutions, namely under the auspices of the Indonesian Ulama Council of North Sumatra which has been established since 2006 and under the auspices of Al-Washliyah University which was established in 2022. The dominant regeneration material is Islamic science based on classical Islamic books (turast). The dominant learning strategy is completing the book, supported by research and community service activities. In the implementation, there are internal constraints in the form of student input, budget limitations and external constraints are the misalignment of internal and government curricula. This research has implications for practical recommendations for Islamic higher education institutions to strengthen their capacity to produce competent scholars